International multidisciplinary collaboration toward an annotated definition of arthrogryposis multiplex congenita. Issue 3 (7th July 2019) - Dahan‐Oliel, Noémi; Cachecho, Sarah; Barnes, Douglas; Bedard, Tanya; Davison, Ann M.; Dieterich, Klaus; Donohoe, Maureen; Fąfara, Alicja; Hamdy, Reggie; Hjartarson, Helgi T.; S. Hoffman, Naimisha; Kimber, Eva; et al.
Abstract: Arthrogryposis multiplex congenita (AMC) has been described and defined in thousands of articles, but the terminology used has been inconsistent in clinical and research communities. A definition of AMC was recently developed using a modified Delphi consensus method involving 25 experts in the field of AMC from 8 countries. Participants included health care professionals, researchers, and individuals with AMC. An annotation of the definition provides more in‐depth explanations of the different sentences of the AMC definition and is useful to complement the proposed definition. The aim of this study was to provide an annotation of the proposed consensus‐based AMC definition. For the annotation process, 17 experts in AMC representing 10 disciplines across 7 countries participated. A paragraph was developed for each sentence of the definition using an iterative process involving multiple authors with varied and complementary expertise, ensuring all points of view were taken into consideration. The annotated definition provides an overview of the different topics related to AMC and is intended for all stakeholders, including youth and adults with AMC, their families, and clinicians and researchers, with the hopes of unifying the understanding of AMC in the international community.